Fabrication and characterization of carboxymethyl chitosan and tea polyphenols coating on zein nanoparticles to encapsulate β-carotene by anti-solvent precipitation method. (April 2018) - Wang, Mei; Fu, Yuying; Chen, Guowen; Shi, Yugang; Li, Xiaomeng; Zhang, Hao; Shen, Yali
Abstract: The aim of this study was to design a colloidal delivery system to encapsulate poor water-soluble bioactive β -carotene so that it could be utilized in various food products as a functional ingredient. A simple anti-solvent precipitation procedure was used to prepare core/shell structure to encapsulate β -carotene with zein, carboxymethyl chitosan (CMCS), as well as tea polyphenols (TP). With the particle size, zeta potential and encapsulation efficiency as main referential indices, the ratio of β -carotene to zein (1:5), carboxymethyl chitosan concentration (0.25 mg/mL) and the concentration of tea polyphenols (0.1 mg/mL) have been systematically optimized. The encapsulated β -carotene was in an amorphous (rather than crystalline form) as detected by differential scanning calorimetry (DSC). Fourier transform infrared (FTIR) indicated that hydrogen bonds and hydrophobic interactions were the major forces responsible for nanoparticles formation. Zein/ β -carotene nanoparticles with CMCS and TP could provide the best controlled release of β -carotene and present the best stability in simulated gastrointestinal conditions. Re-dispersibility in distilled water after freeze-drying, the particle yield was 92.7% higher than zein-CMCS/ β -carotene nanoparticles and zein/β-carotene. In addition, the powders of zein-CMCS-TP/ β -carotene had a fast dissolution rate and the best solubility property. Therefore, we can draw inspiration from this study that zein-CMCS-TP complexes has a potential to be used as a novel stabilizer in colloid delivery systems to encapsulate poor water-soluble bioactive compounds. Graphical abstract: Construct the delivery systems of encapsulating β-carotene by using anti-solvent precipitation technology. Carboxymethyl chitosan as stabilizer and tea polyphenol as cross linker coating the zein nanoparticles.Image Highlights: Constructing core-shell structures to encapsulate β-carotene by anti-solvent method. Zein-carboxymethyl chitosan-teapolyphenol ternary complexes encapsulated β-carotene. Ternary complexes showed good redispersibility in distilled water after freeze-drying. Zein/β-carotene systems showed good DPPH scavenging activity mainly due to stronger hydrophobic interaction. Ternary complexes showed good controlled release profile and markedly improved encapsulation efficiency.